2019
DOI: 10.1002/mp.13671
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Improving VMAT delivery efficiency by optimizing the dynamic collimator trajectory

Abstract: Purpose To provide a method for optimizing the multileaf collimator angle trajectory in volumetric modulated arc therapy (VMAT) in order to make VMAT delivery and planning more efficient. Methods Static fluence maps are optimized at a 10‐degree spacing around the patient. Sliding window delivery time of each of these fields is computed for a large set of possible collimator orientations. An optimal trajectory, which selects a collimator angle for each field and assures that the collimator angles do not differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…This result indicated that the tolerance window setting plays a crucial role in both treatment delivery and planning of the SPArc therapy. Similar conclusions can be found from the previous investigations and clinical implementations of the rotational x-ray therapy, VMAT, in which the tolerance window setting determines the allowable deviation from the ideal dose distribution, affecting the delivery accuracy and treatment efficiency (Bokrantz et al 2019). However, the perturbation effect of uncertainty on dose distribution is more pronounced than it is in photon radiotherapy.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This result indicated that the tolerance window setting plays a crucial role in both treatment delivery and planning of the SPArc therapy. Similar conclusions can be found from the previous investigations and clinical implementations of the rotational x-ray therapy, VMAT, in which the tolerance window setting determines the allowable deviation from the ideal dose distribution, affecting the delivery accuracy and treatment efficiency (Bokrantz et al 2019). However, the perturbation effect of uncertainty on dose distribution is more pronounced than it is in photon radiotherapy.…”
Section: Discussionsupporting
confidence: 84%
“…As we recall the development of volumetric modulated arc therapy (VMAT), numerous investigations were conducted to explore the plan parameters, such as control point sampling frequency and tolerance window settings, and machine characteristics, such as the beam dose rate, gantry angular speed, multi-leaf collimators (MLC) speed with a relationship of treatment delivery accuracy and efficiency (Wang et al 2018, Bokrantz et al 2019, Pokhrel et al 2022. These investigations pave the foundation of the robust and efficient clinical implementation of VMAT, in which a tolerance for MLC positioning of 2.5 mm is recommended, and a tolerance window of 2°is recommended for prostate cancer (Hernandez et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that the VMAT optimization involving sectional optimization of collimator angle could provide delivery efficiency and dosimetric improvements 33 , 34 . Recent studies on the dynamic collimator rotation approach have shown positive results on improving the plan quality 24 , 35 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Bokrantz et al. ( 15 ) provide an optimization method that transfers the collimator trajectory per fluence map to a trajectory per control point of the segmented VMAT plan, which may be integrated in a treatment planning system. MacDonald et al.…”
Section: Introductionmentioning
confidence: 99%